Implementation Of Instilling Ethical Values In Early Childhood At RA Persis 3 Bandung City - Lesmi, Kirana; Khotimah, Iim; Darojatun, Nunun (Jurnal Edusci, 2025)
This study aims to de-research 1) ethical values instilled in early childhood in Ra Persis 3 Bandung City; 2) driving and inhibiting factors in the cultivation of ethical values in Ra Persis 3 Bandung City; 3) efforts to improve the quality of ethics in early childhood Ra Persis 3 Bandung City. In this study, a qualitative approach with a descriptive method is used. The subjects of this study are school principals, educators, and students. Data collection is carried out using observation, interview, and documentation methods. Based on the results of observation and the data collection process using interview techniques, the results of the research show that: 1) the ethical values instilled in early childhood at Ra Persis 3 Bandung City include religious values, the value of manners, the value of cleanliness, the value of social sensitivity and emotions, and the value of honesty and responsibility; 2) The driving factors are competent teachers in their fields, a neatly arranged organizational structure, complete facilities and infrastructure, and learning time that tends to be long when compared to other schools. The inhibiting factors are inadequate funds, students and parents who have various characteristics, and there is no harmony between the school and parents; 3) Efforts to improve the quality of ethics carried out by teachers in instilling ethical values, namely by encouraging children to save, providing good material delivery, providing good examples or examples, and providing parenting, education, and approaches to parents.